Parallel and Distributed Computing and Networks International Conference, PDCN 2010, Chongqing, China, December 13-14, 2010. Revised Selected Papers - Qi, Luo.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the International conference on Parallel and Distributed Computing and Networks, PDCN 2011, held in Chongqing, China, in December 2010. The 19 revised full papers presented were carefully reviewed and selected from numerous submissions. The conference provided a forum for participants from industry, academic, and non-profit organizations to exchange innovative ideas on Parallel and Distributed Computing and Networks related technologies. The papers address current issues in distributed, parallel, ubiquitous, and cloud computing with special focus on systems security, healthcare, and sports economics.
Keywords: Computer science; Medical records -- Data processing; Computer Communication Networks; Software engineering; Data protection; Computer software; Computer Science; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Software Engineering; Systems and Data Security; Health Informatics; Signal, Image and Speech Processing